Massive Hydrothorax and Ascites as the Primary Manifestation of Infection With Clostridium difficile: A Case Report and Literature Review - Liang, Yujian; He, Xiufang; Wang, Ti; Chen, Yili; Huang, Huimin; Tang, Wen; Li, Yijuan (Frontiers in Pediatrics, 2020)
Introduction: Clostridium difficile infection (CDI) is often seen with long term and irregular use of antibiotics. The symptoms of CDI vary but include diarrhea, hypovolemia, electrolyte imbalance, hypoproteinemia, toxic megacolon, gastrointestinal tract perforation, disseminated intravascular coagulation, sepsis, and other lethal complications. The aim of this case report was to present a case of rare clinical manifestation of CDI in a child presenting with massive hydrothorax and ascites. Case Presentation: A 6-year-old girl with a prior history of lymphoma presented with fever 3 days before hospitalization and was treated intravenously with broad-spectrum antibiotics. One day before being hospitalized, she showed persistent fever with abdominal distension and diarrhea. Broad-spectrum antibiotic therapy was initiated after hospitalization and adequate drainage of the hydrothorax and ascites was done. Initially done extensive microbiological evaluation revealed neither any pathogen nor the laboratory tests such as imaging tests or pleural and peritoneal effusion was positive for cancer. Initially, the results from the culture of Clostridium difficile (CD) and detection of the toxin were negative. The patient was diagnosed with CDI only after a positive test result for CD toxin B gene test and repeated stool culture test revealed CDI. Suspension of intravenous antibiotics, oral vancomycin, and Saccharomyces boulardii along with other treatments, resulted in the successful treatment and good outcome. Conclusions: Massive hydrothorax and ascites are rare manifestations of CD-infected patients. CDI is a clinical possibility that should be kept in mind in patients with high-risk factors such as broad-spectrum antibiotic therapy.